Effects of Qigong on Depression: A Systemic Review - Byeongsang Oh (Evidence-Based Complementary and Alternative Medicine, 2013)
Physical exercises and relaxation have been found to be beneficial for depression. However, there is little evidence on the use of Qigong, a mind-body practice integrating gentle exercise and relaxation, in the management of depression. The aim of this paper is to evaluate the effects of Qigong on depression. The paper examined clinical trials measuring the effect of Qigong on depression within six large-scale medical research databases (PubMed, Medline, ProQuest, Science Direct, EMBASE, and PsycInfo) till October 2011. Key words “Qigong,” “depression,” and “mood” were used. Ten studies were identified as original randomized controlled trial (RCT) studies investigating the effect of Qigong on depression as primary (n=2) or secondary outcome (n=8). Four studies reported positive results of the Qigong treatment on depression; two reported that Qigong effect on depression was as effective as physical exercise. One study reported that Qigong was comparable to a conventional rehabilitation program, but the remaining three studies found no benefits of Qigong on depression. While the evidence suggests the potential effects of Qigong in the treatment of depression, the review of the literature shows inconclusive results. Further research using rigorous study designs is necessary to investigate the effectiveness of Qigong in depression.